What Accounts for the US Ascendancy to Economic Superpower by the Early 20th Century: The Morrill Act – Human Capital Hypothesis - Isaac Ehrlich; Adam Cook; Yong Yin (Institute of Labor Economics (IZA), 2018)
Maddison's international panel data show that technically it was the faster growth rate of the US economy that led to its overtaking the UK as economic superpower. We explore the contributing factors. Identifying the land-grant colleges system triggered by the 1862/1890 Morrill Acts (MAs) as a major contributor, we develop this hypothesis theoretically and test it via difference-in-differences regression analyses viewing the MAs as the experiment, the US or US states as treatment groups, and the UK as chief control group in the country-level comparisons. Using national and state-level data, we estimate that the MAs produced sizeable educational and economic returns which catapulted the US into its leading status.
Keywords: N3; E24; H42; I2; O1; O57; O4; 330; aggregate human capital; public investment; education and research institutions; economic development; endogenous growth; institutions and growth; comparative studies of countries; economic history-education